2017
DOI: 10.1007/s10661-017-5889-3
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic concentrations in local aromatic and high-yielding hybrid rice cultivars and the potential health risk: a study in an arsenic hotspot

Abstract: The presence of high levels of arsenic (As) in rice fields has negative effects on the health of those consuming rice as their subsistence food. This study determined the variation in total As concentration in local aromatic rice (LAR) (kalijira) and two high-yielding varieties (HYVs) (BRRI dhan 32 and BRRI dhan 28) grown in paddy fields in Matlab, Bangladesh, an As hotspot with elevated As levels in groundwater. Mature rice grain samples and soil samples were collected from different paddy fields, and the As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Rice and rice-based products with high As concentrations may increase health risk for the humans (Sandhi et al, 2017;Signes-Pastor et al, 2016). The level of total As and As species in rice grains are depended on the rice genotype, physico-chemical, and environmental interactions as summarized in Table 4.…”
Section: Contribution Of Rice To Arsenic Intake In Humansmentioning
confidence: 99%
“…Rice and rice-based products with high As concentrations may increase health risk for the humans (Sandhi et al, 2017;Signes-Pastor et al, 2016). The level of total As and As species in rice grains are depended on the rice genotype, physico-chemical, and environmental interactions as summarized in Table 4.…”
Section: Contribution Of Rice To Arsenic Intake In Humansmentioning
confidence: 99%
“…This arsenic exposure is due to growing food crops in arsenic-contaminated soil and/or irrigated with arsenic-contaminated groundwater. In Bangladesh, rice is one of the major agronomic crop varieties, covering up to 75% of total agricultural land and requiring 83% of irrigation water (Sandhi et al 2017 ). The use of As-contaminated irrigation water in Bangladesh has been found to be the main cause for the accumulation of this carcinogenic metalloid in the food crops (Das et al 2009 ).…”
Section: Arsenic In Food Crops/agriculturementioning
confidence: 99%
“…However, arsenic-related human health risks and their analysis through rice consumption not only depend on the rice varieties, arsenic content in the soil and irrigation water of those cultivated rice fields, and their arsenic AF (accumulation factor, metal/metalloid concentration ratio of plant to soil). A field study conducted in Matlab, Bangladesh, showed that arsenic content in the de-husked grain of hybrid rice cultivars was low compared to the local aromatic rice cultivar and that it could reduce health risk through rice consumption; however, they have a higher accumulation factor than the local rice varieties (Sandhi et al 2017 ). Therefore, the rice cultivars high arsenic AF could increase arsenic ingestion in the human food chain more if they have been cultivated in As-rich environments (soil and groundwater).…”
Section: Arsenic In Food Crops/agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water contamination caused by As is a public health problem in several countries such as Bangladesh, Vietnam and Chile (Smith et al, 2000;Nordstrom, 2002). Recent investigations reported the presence of As in rice grains grown in As prone areas (Sandhi et al, 2017;Maher et al, 2018), heavy metal contamination in fruits and vegetables (Shaheen et al, 2016;Massadeh and Al-Massaedh, 2018) and in soils near an electronics manufacturing facility (Wu et al, 2018).…”
Section: Heavy Metals As Risk Factors For Cvdsmentioning
confidence: 99%